Involvement of the rolled/MAP kinase gene in Drosophila mitosis: interaction between genes of the MAP kinase cascade and abnormal spindle. - Inoue, Y.H.; Glover, D.M. (Molecular and General Genetics, 1998)
We have found that mutations that lead to loss of rolled/MAP kinase function result in a reduced mitotic index in the larval central nervous system, consistent with an interphase block to cell cycle progression, associated with a low frequency of cells showing chromosome over-condensation in mitosis and abnormal anaphase figures. In contrast to wild-type tissue, such rolled mutants do not show a significant increase in accumulation of mitotic cells when treated with colchicine. We have studied double mutant combinations between mutations affecting the activity of rolled/MAP kinase and several genes that are essential to the establishment of a bipolar spindle during progression through mitosis, and find no interactions with mutations in polo, mgr, or aurora. However, partial loss-of-function mutations in rolled enhance the abnormal spindle (asp) phenotype, whereas gain-of function mutations in rolled or in the gene encoding its activating kinase Dsor1, act as suppressors. We discuss these findings in relation to the proposed role of MAP kinase in mediating the spindle integrity checkpoint.